Exploration of Indigenous knowledge in community-based monitoring initiatives : challenges and recommendations - Keats, Beth (2020)
Impact assessment and resource management practices grapple with knowledge and research drawn across paradigms, disciplines, and cultures. In this lies the central challenge of managing developments, especially where Indigenous rights are concerned, and it is this aspect of impact assessment most widely regarded as a failure. The legitimacy of environmental impact assessment rests on the way in which research design and outcomes cope with disciplinary fault lines and different knowledge systems. This thesis explores community-based monitoring (CBM) as an emergent trans-disciplinary methodology for Indigenous knowledge inclusion in resource management. I ask: what are the key challenges of CBM as a pathway for meaningful inclusion of Indigenous knowledge into resource management decisions? I explore this question through a review of literature on the history of Indigenous knowledge and land use research methods and the inclusion of Indigenous knowledge in resource management. Through semi-directed interviews with practitioners, I explore two case studies: the Nunavut Wildlife Management Board Community Based Monitoring Network; and programs run by the Łutsel K’e Dene First Nation in the co-management setting of the Government of the Northwest Territories. Challenges to mobilizing knowledge from Indigenous research participants to co-management resource management decisions are fraught with issues of knowledge authority and epistemological differences, issues of reductionist representation of Indigenous knowledge, interdisciplinary tension, lack of clarity on information needs and research method design, and issues of information control and data autonomy. The CBM programs explored demonstrate active transformation of the legacies of extractive research through the use of technology and data sharing controls that adhere to the principles of Ownership, Control, Access, and Possession (OCAP ®), and by creating information that is gathered by and made legible to Indigenous harvesters. I show that decision-making ...